Natural variation of OsWRKY23 drives difference in nitrate use efficiency between indica and japonica rice - Siyu Zhang; Zhe Ji; Wu Jiao; Chengbo Shen; Yaojun Qin; Yunzhi Huang; Menghan Huang; Shuming Kang; Xuan Liu; Shunqi Li; Zulong Mo; Ying Yu; et al. (Nature Communications)
Abstract Between the two major rice subspecies, indica varieties generally exhibit higher nitrate (NO3 ‒) uptake and nitrogen (N)-use efficiency (NUE) than japonica varieties. Introducing efficient NO3 ‒ utilization alleles from indica into japonica could improve NUE, and at the same time uncover unknown regulators of NO3 ‒ metabolism. Here, we identify OsWRKY23 as a key regulator of NO3 ‒ uptake and NUE differences between indica and japonica rice. The OsWRKY23 indica allele exhibits reduced transcriptional activation of a negative regulator of auxin accumulation, DULL NITROGEN RESPONSE1 (DNR1). The resultant increase in auxin level improves NO3 ‒ uptake and assimilation, which ultimately enhances grain yield. Geographical and evolutionary analyses reveal overlapping distribution of OsWRKY23 indica and DNR1 indica , particularly in low-fertility soils, suggesting their involvement in the adaptation to low N conditions to improve NUE and grain yield. Incorporating the OsWRKY23-DNR1 module from indica rice represents a promising strategy to enhance japonica NUE, which is crucial for sustainable agriculture.